LIQUIDITY, PROFITABILITY, SOLVENCY AND GOING CONCERN AUDIT OPINION ACCEPTANCE: THE ROLE OF FIRM SIZE AS A MODERATION - Dade Nurdiniah (BAKI (Berkala Akuntansi dan Keuangan Indonesia), 2023)
This study aims to analyze the effect of financial performance proxied by liquidity, profitability and solvency on acceptance of going concern audit opinions with firm size as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period and obtained 105 observational data. The data analysis method used in this study is logistic regression analysis and moderation regression analysis. The results showed that liquidity had no effect on acceptance of going-concern audit opinions, profitability had a negative effect on acceptance of going-concern audit opinions, solvency had a positive effect on going-concern audit opinions. Firm size is not able to strengthen the influence of liquidity and profitability on going concern audit opinions, while firm size is able to strengthen the influence of solvency on acceptance of going concern audit opinions.